Not only cardiovascular, but also coordinative exercise increases hippocampal volume in older adults - Niemann, Claudia; Godde, Ben; Voelcker-Rehage, Claudia (Frontiers in Aging Neuroscience, 2014)
Cardiovascular activity has been shown to be positively associated with grey and white matter volume of, amongst others, frontal and temporal brain regions in older adults. This is particularly true for the hippocampus, a brain structure that plays an important role in learning and memory, and whose decline has been related to the development of Alzheimer´s disease. In the current study, we were interested in whether not only cardiovascular activity but also other types of physical activity, i.e., coordination training, were also positively associated with the volume of the hippocampus in older adults. For this purpose we first collected cross-sectional data on “metabolic fitness” (cardiovascular fitness and muscular strength) and “motor fitness” (e.g, balance, movement speed, fine coordination). Second, we performed a 12-month randomized controlled trial. Results revealed that motor fitness but not metabolic fitness was associated with hippocampal volume. After the 12-month intervention period, both, cardiovascular and coordination training led to increases in hippocampal volume. Our findings suggest that a high motor fitness level as well as different types of physical activity were beneficial to diminish age-related hippocampal volume shrinkage or even increase hippocampal volume.